Regional dimension of investment system of the country transformation - Layko, A. (Економічні інновації, 2012)
В статті розглянуті концептуальні засади та методичні рекомендації прикладного характеру щодо трансформації інвестиційної системи країни у відповідності до сучасних вимог і стану розвитку вітчизняної економіки, в контексті її інтегрованості в світогосподарські зв 'язки. The paper is dedicated to the conceptual framework and guidelines to the application of transformation mechanisms for the investment system in the country according to modern requirements and the state of the national economy, in the context of its integration in the world economy. An approach to reforming of the management of the investment process in the direction of supporting the development of the industrial sector as a source of investments regeneration, and delegation of effective state regulation of the investment process in the local (regional) level is proposed. The decentralization of investments infrastructure is expected to use as a catalyst for investment activities by simplifying and expediting of formal- permitting procedures in the implementation of investment projects.